"Nature's contributions to people" and peoples' moral obligations to nature. (June 2022) - Piccolo, John J.; Taylor, Bron; Washington, Haydn; Kopnina, Helen; Gray, Joe; Alberro, Heather; Orlikowska, Ewa
Abstract: The Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES) has become influential in biodiversity conservation. Its research is published widely and has been adopted by the United Nations and the Convention for Biological Diversity. This platform includes discussion about how values relate to biodiversity conservation. The IPBES emphasizes "relational values", connecting these with living a "good life, " and "nature's contributions to people" (NCP); building upon ecosystem services (ES), which have dominated nature valuation for 15+ years. Although the IPBES acknowledges instrumental and intrinsic natural values, they purport that by adopting relational values, conservation will become more socially- and culturally- inclusive, moving beyond the "unhelpful dichotomy" between instrumental and intrinsic values. We wholeheartedly agree that conservation should become more inclusive – it should, in fact, morally include nonhuman nature. We argue that far from being half of an unhelpful dichotomy, intrinsic natural values are incontrovertible elements of any honest effort to sustain Earth's biodiversity. We find NCP to be mainly anthropocentric, and relational values to be largely instrumental. The "good life" they support is a good life for humans, and not for nonhuman beings or collectives. While passingly acknowledging intrinsic natural values, the current IPBES platform gives little attention to these, and to corresponding ecocentric worldviews. In this paper we demonstrate the important practical implications of operationalizing intrinsic values for conservation, such as ecological justice, i.e., "peoples' obligations to nature". We urge the IPBES platform, in their future values work, to become much more inclusive of intrinsic values and ecocentrism.